Optimasi Pemanfaatan Katalis TiO2/Karbon Aktif (Sekam Padi) Untuk Degradasi Methyl Violet Secara Sonolisis dan Fotolisis - Safni, Safni; Aldini, Tasya; Yefrida, Yefrida; Zilfa, Zilfa; Deliza, Deliza (REACTOR: Journal of Research on Chemistry and Engineering, 2024)
The textile industry is a major contributor to pollution, with 10-15% of dyes lost in wastewater during processing, including Methyl Violet. The degradation products of these dyes are often carcinogenic. Conventional biological treatment methods are ineffective due to the complex nature of synthetic dyes. A study aimed to develop a new photocatalytic activity using a UV A lamp and sonolysis using a sonicator. The study modified TiO2/Activated Carbon from Rice Husk as a catalyst to degrade Methyl Violet and textile industry effluent effectively, which was dual benefits as an adsorbent-photocatalyst. Results showed that the degradation by sonolysis and photolysis was 12.99% and 79.16%, respectively. The degradation by photolysis was 14.95% and 94.12%. The light and catalyst with the highest percentage of degradation were TiO2/activated carbon with UV A light of 94.12%. This study aims to develop effective treatment techniques for the textile industry's dyes.